Narrowing the gender gap in rugby injury epidemiology: a novel video-analysis study in the women's game - West, S.; Shill, I.; Patricios, J.; Ainsworth, N.; Everett, A.; George, J.; Sutter, B.; Wiley, P.; Emery, C. (British Journal of Sports Medicine, 2021)
Background Rugby Union has one of the highest risks of injury and concussion in team sports globally. Despite growing participation, little data exists surrounding injury rates and mechanisms in women`s rugby.